Efisiensi penggunaan protein pada puyuh periode produksi yang diberi ransum mengandung tepung daun kayambang - Hesty Rahmawati; Sri Kismiati; Warsono Sarengat (Faculty of Animal Science, Universitas Brawijaya, 2016)
The aim of the experiment was to determine the utilization of kayambang (salvinia molesta) leaves meal on protein consumption, protein efficiency ratio, nitrogen retention, and digestibility protein. Experiment used 200 japanese female quails aged 9 weeks with average body weight 114.86 ± 2.69 g (CV 2.34%). The experiment was conducted in battery cages. The study used a completely randomized design with 4 treatments and 5 replications. The treatment diets were T0 (control), T1 (2.5% Salvinia molesta leaves meal), T2 (5% Salvinia molesta leaves meal) and T3 (7.5% Salvinia molesta leaves meal). The dose of a liquid additive was 5 ml/quail. Observation of crude protein digestibility and the energy was carried for 3 days and protein measurements were analysed using Kjeldahl method. The results showed that administration of salvinia molesta leaf meal up to 7.5% level in the diet decreased the quality of the ration so that the protein utilization was also decreased as indicated by the decline of protein consumption, protein efficiency ratio, nitrogen retention, and digestibility protein. Keywords: quail, kayambang (Salvinia molesta), protein efficiency